Investigating The Impact of Auditor Competence, Independence, and Organizational Culture on Auditor Performance in The Inspectorate of West Bandung District - Anggoro, Reno Fajar (Maksi, 2024)
A world that is connected to each other through digitalization and has an impact on growing economic challenges. Today's world is a very complex system and changes occur quickly among its sub-systems, thus creating pressure to make every effort to anticipate all changes and forms of transformation. In preparation for facing the VUCA challenge, the Indonesian government is trying hard to apply budget discipline and good governance - namely solid and responsible development management that is in line with the principles of democracy and an efficient market, avoiding misallocation of investment funds, prevention of corruption both politically as well as administrative. The implementation of good governance and regional financial management is one manifestation of the implementation of good governance by the government. The government's commitment to good governance needs to pay attention to the performance of government administration, one of which is through an efficient oversight system by expanding the Inspectorate's responsibilities. Skill and independence are abilities that must be driven by appraisers in the inspectorate in supporting good examiner performance, but until now there are still many auditors who do not have adequate skills, independence and culture. The researcher concludes the need for competence, independence and also supported by organizational culture to support good performance to realize good governance (good governance government)